EVALUATION OF RHIZOBIUM AND MYCORRHIZA INTERACTIONS IN SUSTAINABLE MAIZE (Zea mays L.) AND SOYABEAN (Glycine max L.) PRODUCTION (2014)
Maize and soyabean are among the staples in the world. Their sustainable production through the use of synthetic fertilizer causes soil degradation and ground water contamination. An alternative means of boosting and sustaining the production of these staples through the use of rhizobium and mycorrhiza have been reported but there are contradictory reports on interactions between the two organisms. Therefore, the objective of this study was to assess the influence of Rhizobium japonicum and Glomus etunicatum on maize and soyabean production. Three farmlands in Oyo town were purposively selected. In the first and second farmlands were planted sole maize and soyabean respectively and were rotated the following season while both crops were intercropped on the third farmland. The experimental layout was randomised complete block design in split plot with three replications. The treatments were mycorrhizal, rhizobium, combined inoculations and uninoculated (controls). Maize was inoculated with Glomus etunicatum, while soyabean was inoculated with Glomus etunicatum and broth of Rhizobium japonicum. The plants’ population densities were 66,667 and 266,667 respectively. Growth parameters were measured using established methods at two weeks interval. The plants’ biomass, yield, proximate and nutrient analyses were determined using standard methods. Data were analysed using descriptive statistics and ANOVA at p = 0.05. The average heights (cm) of mycorrhiza, rhizobium and combined inoculated plants were 59.8±3.0, 68.3 ±1.8 and 63.7±1.2 respectively while that of their uninoculated counterparts was 52.7±3.4 in both sole and intercropped soyabean. Similarly, significant differences in biomass production were obtained between inoculated (3.7, 3.9, 3.9 g) and uninoculated (2.9 g) soyabean. Sole and rotated soyabean had significant biomass values which were 34.7 and 23.4 % respectively higher than the intercropped soyabean. There was no significant difference in nutrient contents of soyabean; its percentage proximate contents showed significant effects of rhizobium (4.5), mycorrhiza (4.0) or combined inoculation (4.2) in relation to uninoculated treatments (3.1). In intercropped and rotated maize, higher values of number of leaves and plant height were obtained in the mycorrhizal inoculated treatments compared with uninoculated counterparts. Biomass values of the intercropped and rotated maize were 15.5 and 12.5 % respectively higher than that of sole maize. There was significant main effect of mycorrhizal inoculation on nutrient contents of maize in intercropped and rotated farmlands. The grain yields of sole and combined inoculated soyabean ranged between 648.1–738.7 kgha-1 and significantly UNIVERSITY OF IBADAN LIBRARY iii outweighed that of the uninoculated counterparts (524.6–584.9 kgha-1). There were no significant differences in grain yield of sole and intercropped maize, however, grain yield of rotated maize (585 kgha-1) was significantly higher than that of sole maize (512.9 kgha-1). Interactions between R. japonicum and G. etunicatum stimulated growth of both crops, while intercropping enhanced growth and biomass production of maize but had negative effects on soyabean. Interaction between Rhizobium japonicum and Glomus etunicatum had synergistic effects on growth of maize and soyabean. The combination of the two organisms and the systems of farming favoured the yield of both crops. The use of both microsymbionts combined with the cultural farming systems is therefore recommended to boost soyabean and maize production. Keywords: Glomus etunicatum, Rhizobium japonicum, Intercropping, Crop rotation Word count: 499